Performance management in public service organizations: can data be useful to managers even when it is flawed or gamed?. Issue 5 (1st October 2022) - Deschamps, Carl
Abstract: Data quality is seen as a major obstacle to purposeful performance information use by public managers. However, there is a discrepancy between how much managers affirm they care about quality and how much it actually affects their use of performance information. Using interviews of 44 managers in two large public service organizations, we analyze how different facets of data quality really influence managers' ability and willingness to use performance data. We find that, at first, managers focus on issues of credibility, while issues of usability become more important as performance information use proliferate. Managers who engage with data despite its flaws play an important role in owning and fixing data problems, while also creating and leading networks of performance information use. Thus, more often than not, the burden of improving data quality falls on managers rather than being the responsibility of the organization. In short, it is not data quality that encourages data use, but rather managers being willing and able to use performance data that leads to both subjective and objective improvements in data quality.